The Economic Burden of Insulin-Related Hypoglycemia in Adults with Diabetes: An Analysis from the Perspective of the Italian Healthcare System - Parekh, Witesh (Diabetes Ther, 2018)
INTRODUCTION: The aim of this analysis was to estimate the cost of insulin-related hypoglycemia in adult patients with diabetes in Italy using the Local Impact of Hypoglycemia Tool (LIHT), and to explore the effect of different hypoglycemia rates on budget impact. METHODS: Direct costs and healthcare resource utilization were estimated for severe and non-severe hypoglycemic episodes in Italy and applied to the population of adults with type 1 diabetes (T1DM) and type 2 diabetes (T2DM) and their corresponding hypoglycemia episode rates (0.49 severe and 53.3 non-severe episodes per year for T1DM, and 0.09 severe and 9.3 non-severe episodes per year for T2DM). Uncertainty around model inputs was explored through sensitivity and scenario analyses. RESULTS: The direct cost of insulin-related hypoglycemia in Italy is estimated at €144.7 million per year, with €65 million attributable to severe episodes and €79.6 million due to non-severe episodes. The total cost of hypoglycemia is approximately 1.7-fold higher for T2DM (€91.7 million) than for T1DM (€53 million). The cost of a hypoglycemic episode ranges from €4.59 for a non-severe event where additional self-monitoring of blood glucose (SMBG) testing is the only cost incurred, to €5790.59 for a severe event that also requires an ambulance, A&E, hospitalization, and a visit to a diabetes specialist. A reduction in hypoglycemia event rates could result in substantial cost savings; for example, a 20% reduction in severe and non-severe hypoglycemia rates could result in a saving of €47,769 per general population of 100,000 people. CONCLUSIONS: The LIHT highlights the substantial economic burden of insulin-related hypoglycemia in Italy, particularly with regards to non-severe hypoglycemia, an aspect of hypoglycemia that is often overlooked. This analysis may aid healthcare decision-making by allowing the costs of insulin therapies or diabetes self-management programs to be balanced with the savings provided by reductions in hypoglycemia. FUNDING: Novo Nordisk, UK. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13300-018-0418-0) contains supplementary material, which is available to authorized users.